Analisis Komparatif Penolakan Hak Waris dalam Perspektif Hukum Islam (KHI) dan KUHPerdata di Indonesia - Iftina Tristya Sari; Al Qodar Purwo Sulistyo (Jurnal Ilmiah Penegakan Hukum, 2026)
This study aims to comparatively analyze the regulation of the renunciation of inheritance rights under Islamic Law, as codified in the Compilation of Islamic Law (KHI), and under Civil Law, as regulated in the Indonesian Civil Code (KUHPerdata). These two legal systems coexist in Indonesia and provide distinct frameworks for heirs to renounce inheritance, in terms of the legal basis, procedures, and consequences. This research employs a normative juridical method, drawing on statutory and comparative approaches and supported by primary and secondary legal materials. The findings indicate that under the Civil Code, renunciation of inheritance must be explicitly declared before a District Court and is absolute, resulting in the heir being considered never to have existed in the line of succession. In contrast, under KHI, renunciation is effected through the mechanism of takharuj, based on mutual agreement among heirs, without eliminating the heir's legal status. These differences significantly affect inheritance rights, especially concerning the descendants of the renouncing heir. This study highlights that the Civil Code emphasizes legal certainty and individual protection, whereas Islamic Law prioritizes deliberation, equity, and family protection.